Flexural properties of copper-filled carbon fiber reinforced polymers; IOP Conference Series: Materials Science and Engineering; Vol. 1118 : Mechanical Engineering and Modern Technologies (MEMT 2020) - Eremin A. V. Alexandr Vyacheslavovich (2021, 2021)
Title screen